Experimentelle Untersuchung und Simulation des Umformverhaltens nähgewirkter unidirektionaler Kohlenstofffasergelege - Schirmaier, Fabian (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2017)
In this work experimental tests are performed to investigate the forming behavior of unidirectional non-crimp fabrics (UD-NCFs) within the context of an automated preforming process. Based on the experimental results, a macroscopic forming simulation model for UD-NCFs is developed and model parameters are identified via the simulation of material tests. The forming simulation model is validated via hemisphere and car body part forming tests.